Historical school stories: tensions and challenges for the formation of the citizen subject in secondary school (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2025)
Starting from a dialogue between the contributions of the history of education and the teaching of history, in this work I analyze the historical stories present in the curricular materials of history teachers of a secondary school in the Province of Buenos Aires. From this I warn and reflect on some tensions and challenges that these stories present to think about the formation of the citizen subject for democratic life. I am particularly interested in investigating and analyzing how from school, especially from the teaching of history, senses of citizen identity and with it a way of being a subject are transmitted through historical stories. In the first part, I develop the theoretical methodological framework built, from a framework between Latin American and European authors, to be able to carry out the analysis of the historical stories. Later I address some historical stories that history teachers used for their classes.
Keywords: school; citizen training; historical stories; curricular materials